The spatial economics of energy justice: modelling the trade impacts of increased transport costs in a low carbon transition and the implications for UK regional inequality. (May 2020) - Olner, Dan; Mitchell, Gordon; Heppenstall, Alison; Pryce, Gwilym
Abstract: Spatial economic change is an energy justice issue (Bouzarovski and Simcock, 2017) - an essential consideration in how we choose to re-wire the economy for a carbon-free future. Nothing like the conscious system-wide change required has been attempted before. Rapid policy decisions risk embedding existing injustices or creating new ones unless steps are taken to ameliorate those risks. We present a model that takes a whole-system view of the UK spatial economy, examining how increasing distance costs (e.g. through fuel tax hikes) have unequal impacts on regions and sectors. The model establishes an important carbon transition policy principle: change in spatial flows of internal trade, which are certain to occur rapidly during transition, have measurable energy justice implications. Peripheral economic regions, in rural and coastal areas and many city outskirts are most vulnerable, as are petrochemical, agricultural and connected sectors. Policy must go beyond identifying places and sectors most affected: it is the connections between them that matter most. The "push" of spatially aware fiscal policy needs to be combined with the "pull" of targeted interventions designed to promote low-carbon intermediate connections. This is not only just, but would help make (potentially costly) transition more politically acceptable. Highlights: Change in spatial flows of internal trade have measurable energy justice implications. Re-wiring the economy for a carbon-free future should consider this to avoid creating new losers. Peripheral regions in rural, coastal areas and many city outskirts are most vulnerable. Petrochemical, agricultural and connected sectors are most affected by distance cost change. Spatially aware fiscal policy needs combining with targeted low-carbon intermediate trade links.